Unexpected Reactivity of Red Phosphorus in Ionic Liquids (Eur. J. Inorg. Chem. 24/2015). Issue 24 (August 2015) - Groh, Matthias F.; Paasch, Silvia; Weiz, Alexander; Ruck, Michael; Brunner, Eike
Abstract : The cover picture shows the enhanced reactivity of red phosphorus in the employed ionic liquid. Dissolved iodine molecules (yellow spheres) etch red phosphorus, which results in either molecular iodides, for example PI3, or phosphorus nanoparticles. The formation of the different species is monitored by liquid‐ (top) and solid‐phase (bottom) NMR spectroscopy. Details are discussed in the article by M. Ruck, E. Brunner et al. onp. 3991 ff . For more on the story behind the cover research, see theCover Profile .